2018
DOI: 10.1371/journal.pone.0208742
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with infections and augmented renal clearance: A multicenter retrospective study

Abstract: Recently, augmented renal clearance (ARC), which accelerates glomerular filtration of renally eliminated drugs thereby reducing the systemic exposure to these drugs, has started to receive attention. However, the clinical features associated with ARC are still not well understood, especially in the Japanese population. This study aimed to evaluate the clinical characteristics and outcomes of ARC patients with infections in Japanese intensive care unit (ICU) settings. We conducted a retrospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…The patients with ARC in the present study accounted for 14.9% of the sample, and a higher BMI and lower serum creatinine level were independent predictors of ARC. Recently, Kawano et al 28 reported that the incidence of ARC was only 6.8% in 280 Japanese patients in the ICU, which was much lower than that found in other studies. However, that study involved many elderly patients, with a median age of 74 years, and the oldest patient was 106 years old.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The patients with ARC in the present study accounted for 14.9% of the sample, and a higher BMI and lower serum creatinine level were independent predictors of ARC. Recently, Kawano et al 28 reported that the incidence of ARC was only 6.8% in 280 Japanese patients in the ICU, which was much lower than that found in other studies. However, that study involved many elderly patients, with a median age of 74 years, and the oldest patient was 106 years old.…”
Section: Resultsmentioning
confidence: 71%
“…The relatively few young patients in that study could, therefore, account for the lower prevalence of ARC. The study by Kawano et al 28 also used estimated glomerular filtration‐rate values that were calculated by a Japanese equation for evaluating ARC and that equation was reported to underestimate the glomerular filtration rate in ICU settings. The use of different assessment techniques, such as various equations for diagnosing ARC, might have yielded different results for the incidence of ARC.…”
Section: Resultsmentioning
confidence: 99%
“…A threshold CrCl of ≥ 170 ml/min was associated with beta-lactam antibiotic underdosing and more therapeutic failures [ 18 ]. Contrarily, other studies did not find an association between ARC-induced beta-lactam antibiotics renal elimination enhancement and mortality, which could be explained by the low prevalence of ARC in the population studied and the use of combination therapy, which could obscure the effect of ARC on clinical outcomes [ 13 , 16 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 87%
“…In the analysis cohort, ARC did not affect mortality (Table 4). Previous studies have also reported that ARC reduces the internal concentration of antibiotics but does not exacerbate overall mortality 5,6,25,26 . This observation may be related to the fact that ARC is more likely to occur in patients with less severe conditions 6 .…”
Section: Discussionmentioning
confidence: 91%
“…ARC is commonly observed in 14%–80% of the patients in intensive care units (ICU) 1 . Certain risk factors for ARC in ICU patients, for example, young age (<50 years), male sex, trauma and traumatic brain injury, have been identified 1,3‐6 …”
Section: What Is Known and Objectivementioning
confidence: 99%